Impedance spectroscopy of polyaniline coated hydrogel - Okutan, Mustafa; Yavuz, Erdem; Ozerol, Esma Ahlatcioglu; Senkal, B. Filiz; Yalcin, Orhan; Yildiz, Alptekin (SPRINGER, 2021)
A sulfonic acid functional hydrogel was prepared starting from the copolymerization of 2-acrylamido-2-methyl-1-propanesulfonic acid as monomer and tetraallyl ammonium bromide as a cross-linking agent in the presence of K(2)S(2)O(8)as a radical initiator. Aniline was interacted with the hydrogel, and oxidative polymerization reaction of anilinium sulfonate salt containing hydrogel was performed by using ammonium persulfate to obtain conducting gel material. The electrical/dielectric properties of the PANI-coated hydrogel were analyzed using impedance spectroscopy. The frequency dependence of the real (epsilon ') and imaginary (epsilon '') parts of the dielectric constant (epsilon), dissipation factor, the real (sigma ') and imaginary (sigma '') parts of the ionic conductivity (sigma), Cole-Cole plots and impedance parameters values for the PANI-coated hydrogel were analyzed in the frequency range of 100 Hz-15 MHz at room temperature. PANI-coated hydrogel shows the non-Debye relaxation type in the materials. The conductivity mechanisms of PANI-coated hydrogel are super linear power law and extended pair approximation.
Keywords: PANI; Dielectric properties; Conducting gel; Hydrogel; IMMOBILIZATION; NANOPARTICLES; COMPOSITES; POLYMERS; Polymer Science